The retinal pigment epithelium: Functions and roles in ocular diseases - Shasha Wang; Wanhong Li; Min Chen; Yihai Cao; Weisi Lu; Xuri Li (Fundamental Research)
The retinal pigment epithelium (RPE) between retinal photoreceptors and choroidal capillaries is a single layer of cells that are of critical importance to the eye. RPE cells are derived from the anterior neural plate of neuroectodermal origin. Instructed by specific molecules and signaling pathways, the RPE undergoes formation and maturation to form a functional unit together with photoreceptors. The RPE plays crucial roles in maintaining normal retinal structure and functions, such as phagocytosis; barrier function; transportation of nutrients, ions, and water; resistance to oxidative damage; maintenance of visual cycle; and production of various important factors. RPE cells have an efficient metabolic machinery to provide sufficient energy to the retina. RPE dysfunction or atrophy can lead to many retinopathies, such as age-related macular degeneration and proliferative vitreoretinopathy. Here, we discuss RPE development, functions, and roles in various ocular diseases, and the mechanisms involved. A better understanding of the functions of the RPE and related regulatory pathways may help identify novel or better therapies for the treatment of many blinding diseases.